The Oxford handbook of land economics - Duke, Joshua M.; Wu, Junjie (College teacher) (New York : Oxford University Press, 2014)
Land use change is one of the most pervasive socioeconomic forces affecting ecological systems, economic systems, and human wellbeing. This handbook draws on recent advances in several economic fields that investigate land use behaviour, making this a must-read for those who want to understand the frontier of land economics.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on August 27, 2014).
Keywords: Land use; Economic development